HRD Communication in Improving Employee Performance at General Hospital: Komunikasi HRD dalam Meningkatkan Kinerja Karyawan di Rumah Sakit - Mawahda, Sindi Risky; Sinduwiatmo, Kukuh (Indonesian Journal of Innovation Studies, 2023)
HRD is a department within an organization whose function is to plan, organize, direct and procure, control, develop, maintain, discipline, and terminate. All employees in an organization will be covered by HRD starting from recruiting employees and handling all employee complaints. The formation of the quality of employee work is also due to the encouragement made by HRD so that employees can further improve the quality of their work to be able to carry out their duties and responsibilities as well as possible in accordance with the goals set by the organization. An HRD must be able to place a communication position that is applied with an open nature and nothing is hidden or covered regarding work and company matters, for the sake of mutual interest and progress, although open communication does not necessarily provide the best guarantee for the company. The method in this study uses qualitative research. The data sources used in this study are primary and secondary data sources. The methods of data collection used in this study were observation, interviews and documentation. The analysis technique that the researcher uses is descriptive analysis method. The results showed that the HRD of Rsu Jasem Sidoarjo had open and active communication. The role of the leader is quite good in carrying out their duties and responsibilities. The performance of the employees of the Jasem Sidoarjo Hospital based on the results of the Employee's annual report, has experienced an increase in hospital visitors in the last 3 years.